Effect of three filler types on mechanical properties of dental composite - Pahlavan A.; Ataei M.; Zandi-Nejad AA (Tehran University of Medical Sciences, 2005)
Statement of Problem: Despite the improvements achieved in the field of dental composites, their strength, longevity, and service life specially in high stress areas is not confirmed. Finding better fillers can be a promising step in this task. Purpose: The purpose of this study was to investigate the effect of the filler type on the mechanical properties of a new experimental dental composite and compare these with the properties of composite containing conventional glass filler. Materials and Methods: Experimental composites were prepared by mixing silane-treated fillers with monomers, composed of 70% Bis-GMA and 30% TEGDMA by weight. Fillers were different among the groups. Glass, leucite ceramic and lithium disilicate were prepared as different filler types. All three groups contained 73% wt filler. Comphorquinone and amines were chosen as photo initiator system. Post curing was done for all groups. Diametral tensile strength (DTS), flexural strength and flexural modulus were measured and compared among groups. Data were analyzed with SPSS package using one-way ANOVA test with P<0.05 as the limit of significance. Results: The results showed that the stronger ceramic fillers have positive effect on the flexural strength. Ceramic fillers increased the flexural strength significantly. No significant differences could be determined in DTS among the groups. Flexural modulus can be affected and increased by using ceramic fillers. Conclusion: Flexural strength is one of the most significant properties of restorative dental materials. The higher flexural strength and flexural modulus can be achieved by stronger ceramic fillers. Any further investigation in this field would be beneficial in the development of restorative dental materials.